قانون مناهضة العنف الأسري في إقليم كوردستان العراق : دراسة فقهية تقويمية - كوجري، رضوان حازم خالد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research addresses the law of resistance to family violence in Kurdistan, Iraq. The law triggered a huge polemic in the judiciary and legislative milieus as it is founded on the concept of gender. This study aimed at clarifying the concept of domestic violence and exposing the stated cases in the above mentioned law for evaluation in light of Islamic jurisprudence. To this end, the researcher used an inductive approach to gather the scientific substance and analysed these cases through an analytical method. The findings of the research demonstrate that the law has been sometimes weakly formulated, holds poor expressions, lacks details in regards to the wording of texts and occasionally violates Islamic rulings. These issues call for a reassessment of the legislator's knowledge on Shari'ah rulings, law, language, psychology and sociology by the government of the Kurdistan region of Iraq.